The Economic Sociology of Development - Schrank, Andrew (Economy and society series (Cambridge, England), 2023)
Schrank draws concrete examples from different regions and epochs to explore sociological thinking about development and underdevelopment informed by the latest currents in economic sociology. Across a series of chapters, he identifies relationships between mainstream and Marxist approaches to the study of international inequality; uses classical and contemporary social theory to develop a parsimonious typology of national development outcomes; addresses cross-border learning and diffusion in light of the latest developments in organisation theory; considers the roles of religious, racial, and gender identity in driving development in different places and times; and portrays contemporary global challenges - such as populism, pandemics, and climate change - as distinctly sociological problems in need of multifaceted solutions.